Fixing the GAP: The role of RhoGAPs in cancer - Gabriel Kreider-Letterman (European Journal of Cell Biology, 2022)
Cancer progression and metastasis are processes that involve significant cellular changes. Many of these changes include alterations in the activity of the Rho GTPase family of proteins. Rho GTPases are signaling proteins that function as molecular switches and are involved in the regulation of most major cellular processes. Cancer development is often associated with abnormalities in Rho GTPase signaling. Rho GTPase signaling is regulated by two families of proteins, guanine nucleotide-exchange factors (RhoGEFs) and GTPase activating proteins (RhoGAPs), that function upstream of the Rho proteins to regulate their activation and inactivation, respectively. While initial work has focused on the role of RhoGEFs in cancer, the RhoGAP family members are rapidly being established as key regulators of cancer development and progression. The aim of this review is to summarize our advances in understanding the role of RhoGAPs in cancer and to discuss their significance in the development of therapeutics.